1999
DOI: 10.1084/jem.189.4.647
|View full text |Cite|
|
Sign up to set email alerts
|

Treponema pallidum Major Sheath Protein Homologue Tpr K Is a Target of Opsonic Antibody and the Protective Immune Response

Abstract: We have identified a family of genes that code for targets for opsonic antibody and protective immunity in T. pallidum subspecies pallidum using two different approaches, subtraction hybridization and differential immunologic screening of a T. pallidum genomic library. Both approaches led to the identification of a polymorphic multicopy gene family with predicted amino acid homology to the major sheath protein of Treponema denticola. One of the members of this gene family, tpr K, codes for a protein that is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
222
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(230 citation statements)
references
References 45 publications
6
222
0
Order By: Relevance
“…The recent complete T. pallidum genome sequence (Fraser et al, 1998) revealed that the T. pallidum chromosome encodes 12 polypeptides with sequence relatedness to the major outer sheath of T. denticola (Centurion-Lara et al, 1999). Comparison of the T. pallidum genome sequence with that of B. burgdorferi identified unique and common genes and substantiates the considerable diversity observed among pathogenic spirochetes.…”
mentioning
confidence: 93%
“…The recent complete T. pallidum genome sequence (Fraser et al, 1998) revealed that the T. pallidum chromosome encodes 12 polypeptides with sequence relatedness to the major outer sheath of T. denticola (Centurion-Lara et al, 1999). Comparison of the T. pallidum genome sequence with that of B. burgdorferi identified unique and common genes and substantiates the considerable diversity observed among pathogenic spirochetes.…”
mentioning
confidence: 93%
“…Although T. pallidum has few integral outer membrane proteins (23,24,77,78), bioinformatic approaches have identified several candidates, including members of the family of 12 T. pallidum repeat (Tpr) proteins (79,80). Among Tpr family members, TprK is the best studied.…”
Section: The Natural History Of Syphilis Primary Syphilis -Transmissimentioning
confidence: 99%
“…The amplicons from T. pallidum Seattle Nichols strain DNA were cloned into the pRSET expression vector (Invitrogen, Carlsbad, CA), the sequence was verified, and the peptide was expressed in Escherichia coli and purified as previously described (7,13). The proteins were dialyzed into PBS, pH 7.2, size confirmation and purity were evaluated by SDS-PAGE, and concentrations were determined using a bicinchoninic acid protein assay (Pierce, Rockford, IL).…”
Section: Immunizationmentioning
confidence: 99%
“…In the search for T. pallidum subspecies pallidum virulence factors, members of a family of 12 genes called Treponema pallidum repeat (tpr) 3 genes A-L were identified (7)(8)(9). In an organism that lacks major biosynthetic capacity, devoting 2% of its small genome to the tpr gene family is quite remarkable and suggests the importance of the tpr gene family to the organism.…”
mentioning
confidence: 99%
See 1 more Smart Citation